Intermediate accounting - Sepe, James F. (United States of America. Irwin McGraw-Hill., 1998)
"The role of financial reporting is to communicate information that supports business decesion making. Without understanding how decision makers use accounting information, it is difficult for accounting students to fully understand financial reporting issues or, more importantly, to critically evaluate reporting alternatives. A stated objective of the most intermediate accounting textbook is to achieve an appropriate balance between procedures and theory. We share this objective, but do not feel that there necessarily is a tradeoff between the "why" and the "how." Instead, we believe that a true understanding of how a particular procedure is applied demands a clear understanding of why it is applied. Without a through comprehension of the basis for its application, students merely memorize the mechanics of a procedure. Students have a learned tendency to memorize. Traditional presentation often does little to dissuade that tendency."
Include index.
English text.
Keywords: Accounting